Press Consumption in the Digital Age: Habits and Needs Regarding Online Press - Fernandes, F.; Alturas, B. (Proceedings of the Academy of Marketing Annual Conference 2013: Marketing Relevance, 2013)
This paper addresses the topic of Online Press and the challenge that the press faces to maintain its predominance as a communication media, before a public with new aptitudes, access to new technologies and, above all, to a wider and more dynamic range of alternative communication sources. This study is based on the principle that the solution for a sustainable and attractive marketing strategy for the press, starts with the comprehension of the way its public perceives the products made available by the publishers, of its needs as for the information consumption, as well as of the familiarity it has with the information technologies. Resorting to an online questionnaire inquiry to 330 individuals, we gathered information about their newspaper and magazine reading habits, their consumption of press products and technological aptitudes.